Turbidity analysis and its causes of four young bottled red wines - SONG Ying, LIU Yuzhou, SHI Rui, LI Wanxin, GUO Anque (Zhongguo niangzao, 2024)
The appearance of turbidity and sedimentation during wine storage, transportation and sale, can seriously affect the sensory quality and the shelf-life of wine. Using four turbid young bottled red wines (turbid and lusterless) as test materials, the turbid types were examined by microscope, and the physicochemical indexes and sensory characteristics of the wine samples were systematically analyzed. The characteristics and possible causes of turbid in young bottled red wines were discussed. The results showed that non-biological turbidity was responsible for the turbid wine samples. Besides tartar precipitate, there were also pigmentation and iron precipitation. All four samples tested exhibited aged characteristics both in color and aroma. The samples were brownish-red in color with a prominent yellow hue (b*), and the polymeric anthocyanins accounted for 76.61% to 82.16% of the total anthocyanins, while with only 6.54% to 7.90% of the monomeric anthocyanins. Aged aromas such as toast and spice odors were dominant, and with a lack of grape varietal aromas, and oxidized and acetic acid notes in some cases. The results of correlation analysis further suggested that the aging of wine samples was largely related to the oxidation of wine samples during storage. Suitable storage conditions might be crucial to stabilize the quality of young bottled red wines.